The Problem of Fiscal Direction of the Code of Russian Federation on Administrative Offences and Ways of its Solution in Draftof the New Code of the Russian Federation on Administrative Offences - A. A. Grishkovets (Сибирское юридическое обозрение, 2019)
The article considers the problem of fiscal orientation of the Code of the Russian Federation on administrative offenses. An analysis of the practice of applying the Code’s norms shows that administrative jurisdictions often impose an administrative penalty such as a fine as part of their control and supervision activities. In modern Russia, administrative fines have become a source of significant non-tax revenue for the budgets of the country's budget system. This situation allows us to talk about the fiscal focus of the Code of the Russian Federation on administrative offenses, while the objectives of administrative punishment are private and general prevention. It is concluded that there is a need to defiscalize the new Code of the Russian Federation on administrative offenses.